Groundwater Occurrence and Aquifer Classification in En Nuhud Basin, Kordofan Region, Sudan - A Elmansour, Asim; G Elseed, Elnazir; A Elhadi, Mohamed (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 6 No 3&4 (2019): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
En Nuhud basin is the only source for water supply in a wide, densely populated and economically important area. The study aims to evaluate the hydrogeological environment and to highlight the critical factors that affect groundwater occurrence in En Nuhud basin. Integration of borehole data with geophysical investigations, in addition to pumping tests was used to achieve the mentioned objectives. The main and hydrogeologically important unit in the study area is the Nubian Sandstone Formation; conglomerates and sandstones represent the main distinguishable aquifers. Basement Complex when it is weathered enough to form secondary porosity and when it is close to the upper saturated sediments, serves the purpose of circulating and accumulating groundwater. Generally the depth of productive wells in the area ranges from 90 to 410 m and mostly the drilled wells within the sedimentary sequence less than 100 m are failed. No Perched water is recorded due to the high permeability of the upper formations. Regarding the thickness of the aquiferous zone, it ranges from 10 to 140 m. The aquifers in the study area were classified into two categories; unconfined aquifers that dominate the northern half of the area and they found to be relatively shallow to medium in depth; confined aquifers dominate the southern part and they usually related to the deep sedimentary sequence or found when multi-layered aquifer occurs. How to cite this article: Elmansour AA, Elseed EG, Elhadi MA. Groundwater Occurrence and Aquifer Classification in En Nuhud Basin, Kordofan Region, Sudan. J Adv Res Geo Sci Rem Sens 2019; 6(3&4): 27-35.